2014
DOI: 10.1186/1471-2458-14-148
|View full text |Cite
|
Sign up to set email alerts
|

Can food vouchers improve nutrition and reduce health inequalities in low-income mothers and young children: a multi-method evaluation of the experiences of beneficiaries and practitioners of the Healthy Start programme in England

Abstract: BackgroundGood nutrition is important during pregnancy, breastfeeding and early life to optimise the health of women and children. It is difficult for low-income families to prioritise spending on healthy food. Healthy Start is a targeted United Kingdom (UK) food subsidy programme that gives vouchers for fruit, vegetables, milk, and vitamins to low-income families. This paper reports an evaluation of Healthy Start from the perspectives of women and health practitioners.MethodsThe multi-method study conducted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
105
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(113 citation statements)
references
References 29 publications
7
105
0
1
Order By: Relevance
“…Women who fed their babies using formula reported spending all or nearly all of their vouchers on formula 10 15 22. There may therefore be differential effects on diets of families purchasing infant formula compared with breastfeeding women, given that formula costs more than the value of vouchers 10. However, restricting the sample to exclude families with children aged under 1 did not change the overall findings: while F&V varied by eligibility and year, there was no significant interaction, indicating that there was not a significantly different rate of change for the HS-eligible group compared with the others.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Women who fed their babies using formula reported spending all or nearly all of their vouchers on formula 10 15 22. There may therefore be differential effects on diets of families purchasing infant formula compared with breastfeeding women, given that formula costs more than the value of vouchers 10. However, restricting the sample to exclude families with children aged under 1 did not change the overall findings: while F&V varied by eligibility and year, there was no significant interaction, indicating that there was not a significantly different rate of change for the HS-eligible group compared with the others.…”
Section: Discussionmentioning
confidence: 86%
“…A large qualitative study with HS stakeholders reported that HS is perceived to provide a nutritional safety net for low-income families 10. Our study sought to identify any association between the introduction of HS and F&V intake among eligible families compared with that of the control groups, using data from the HSE.…”
Section: Introductionmentioning
confidence: 99%
“…The numbers of patients admitted to hospitals for malnutrition rose from 3000 in 2008 to 5500 during 2013(Channel 4 News, 8.12.2013. Families are at risk of malnutrition because they are unable to purchase healthy food items (Maslen, Raffle, Marriot, & Smith, 2013;McFadden et al, 2014;Wickham et al, 2016).…”
Section: Food Banks In the Ukmentioning
confidence: 99%
“…). Families are at risk of malnutrition because they are unable to purchase healthy food items (Maslen, Raffle, Marriot, & Smith, ; McFadden et al, ; Wickham et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the UK, no conclusive results were found. In some cases changes in consumption or purchasing behaviour were not observed (15) , while in other cases both quantity and variety of food were improved by interventions based on vouchers (16,17) . There are cases in which more than one intervention was tested, usually including nutritional training or advice and the use of vouchers.…”
mentioning
confidence: 99%